Original articleGender differences in serum cortisol levels among patients with major depressive disorder - Sanches, Marsal; Zunta-Soares, Giovana B; Hatch, John P; Soares, Jair C (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2013)
Introduction : A large amount of evidence supports the involvement of the hypothalamic-pituitary-adrenal axis (HPA) in the pathophysiology of mood disorders. These findings seem to reflect hyperactivity of the HPA axis in depression and are likely related to impaired negative feedback by endogenous glucocorticoids. However, any gender differences related to this involvement are unclear. Material and methods : We collected serum cortisol samples of 71 unmedicated patients with major depressive disorder (21 males, 50 females; age = 38.85 ±13.66) and 60 healthy controls (19 males, 41 females; age = 33.25 ±11.79). All patients met the DSM-IV-R criteria for major depressive disorder, confirmed through the Structured Clinical Interview for DSM Disorders (SCID). Comparisons of the mean cortisol levels between groups were carried out using factorial analysis of covariance, with age and body weight as covariates. Results: There was a statistically significant interaction between diagnosis and gender (F = 6.72, d.f. = 1/109, p = 0.01). Male patients had significantly higher cortisol levels compared to male controls (patients = 12.33 ±3.63 µg/dl, controls = 10.16 ±3.44 µg/dl; F = 6.25, d.f. = 1/35, p = 0.01) whereas female patients had nonsignificantly lower cortisol levels compared to female controls (patients = 9.88 ±3.03 µg/dl, controls = 11.79 ±5.70 µg/dl; F = 2.68, d.f. = 1/83, p = 0.10). Conclusions: Although preliminary, our findings suggest that gender may in part moderate HPA dysfunction in major depressive disorder. Further studies are necessary in order to replicate these findings and investigate their true implications.